REACTİVE BLUE 19 VE REACTİVE YELLOW 145 BOYARMADDELERİNİN TEKLİ VE İKİLİ SİSTEMDE SULU ÇÖZELTİLERDEN UZAKLAŞTIRILMASI - ÇAKMAK, TUĞCAN (Fırat Üniveristesi, 2016)
Bu tez çalışmasında Türkiye tekstil endüstrisi atıksularında sıkça karşılaşılan reaktif boyarmaddelerden Reactive Blue 19 (RB19) ve Reactive Yellow 145 (RY145) ile RB19- RY145 ikili karışımlarının çiğit küspesi ile adsorpsiyonu kesikli sistemde incelenmiştir. Deneysel çalışmalarda her bir boyarmadde için adsorpsiyon hız ve kapasitesine, başlangıç pH'ının, sıcaklığın ve başlangıç boyarmadde konsantrasyonunun etkileri incelenmiştir. RB19 ve RY145 reaktif boyarmaddelerinin çiğit küspesi ile adsorpsiyonunda optimum pH değeri 1.5 olarak saptanmıştır. Optimum sıcaklık 20 ºC olarak seçilmiştir. RB19 ve RY145 boyarmaddelerinin yüzde giderimi boyarmadde konsantrasyonlarının artmasıyla azalmış, adsorbent dozunun arttırılmasıyla artmıştır. Her bir kirletici sistem için farklı sıcaklıklarda (20, 30, 40 ve 50 ºC) yapılan deneylerin sonuçları Langmuir ve Freundlich izotermlerine uygulanmış, model sabitleri hesaplanmıştır. Adsorpsiyon dengesinin Langmuir izoterm modeline daha iyi uyduğu belirlenmiştir. Adsorpsiyon mekanizmasını araştırmak üzere deneysel verilere çeşitli kinetik modeller uygulanarak kinetik sabitler de bulunmuştur. Elde edilen sonuçlar adsorpsiyonun yalancı II. derece kinetik modele daha iyi uyduğunu göstermiştir. Bu çalışmada prosesin entalpi değişimi (?Hº) RB19 ve RY145 boyarmaddeleri için sırasıyla 20.10 ve 12.50 kj/mol olarak hesaplanmıştır. Entalpi değişiminin pozitif olması RB19 ve RY145 boyarmaddelerinin çiğit küspesi ile adsorpsiyonunun endotermik olduğunu gösterir. RB19 ve RY145 boyarmaddeleri için hesaplanan serbest enerji değişimi (?Gº) değerleri ise negatif işaretlidir ve artan sıcaklıkla mutlak değeri artmıştır. RB19-RY145 ikili karışımlarının çiğit küspesine adsorpsiyonu çeşitli sıcaklıklarda incelenmiş, boyarmaddelerden birinin derişimi sabit tutulurken diğer boyamaddenin derişimi değiştirilerek, birinci bileşenin ikinci bileşenin adsorpsiyonunun dengede birim adsorbent kütlesi basına adsorplanan miktarını nasıl etkilediği araştırılmıştır. Ortamdaki RY145 boyarmadde iyonlarının varlığının RB19 adsorpsiyonunu azalttığı gözlenmiştir. RB19-RY145 ikili karışımları için farklı sıcaklıklarda yapılan deneylerden elde edilen sonuçların da Langmuir izoterm modeline uyduğu ve adsorpsiyon kinetiğinin de yalancı II. dereceden kinetik modele uyduğu belirlenmiştir. İkili karışım için hesaplanan entalpi değeri tek bileşenli sistemde hesaplanan entalpi değerinden küçük bulunmuştur. Buna ek olarak, ikili karışım için hesaplanan serbest enerji değişiminin mutlak değeri de tek bileşenli sistem için hesaplanan değerden küçük bulunmuştur. Anahtar Kelimeler: Reactive Blue 19, Reactive Yellow 145, Boyarmadde, Adsorpsiyon, Çiğit küspesi.

In this thesis study, the biosorption of single and binary combinations of Reactive Blue 19 (RB19) and Reactive Yellow 145 (RY145) reactive dyes, which are frequently encountered in Turkish textile industry wastewaters, was investigated in a batch system with cottonseed pulp. In experimental studies, the effects of initial pH, temperature and initial dye concentration on the adsorption rate and capacity were examined in a batch system. In the adsorption of RB19 and RY145 dyes onto cottonseed pulp biosorbents, the optimum pH value was determined as 1.5. Optimum temperature is 20 ºC. The removal percentage of RB19 and RY145 dyes were reduced by increasing the of the dye concentration and increased by increasing the adsorbent dose. The results of the experiments carried out at various temperatures (20, 30, 40 and 50 ºC) the Langmuir and Freundlich adsorption models were applied to each pollutantsorbent system in order to define the adsorption equilibrium data mathematically. The model constants were determined and it was determined that the adsorption equilibrium data showed on excellent description to the Langmuir isotherm model. The kinetic constants were evaluated by applying different kinetic models to experimental data in order to investigate the adsorption mechanism. It was determined that the adsorption data showed on excellent description to the pseduo-second-order model. In the study enthalpy changes (?Hº) for adsorption processes of RB19 and RY145 dyes were calculated as 20.10 and 12.50 kJ/mol, respectively. That the enthalpy changes of process for are positive a with that the adsorption process of RB19 and RY145 dyes by cottonseed pulp is endothermic. The free energy changes related to the RB19 and RY145 dyes adsorption by cottonseed pulp have negative sign and the absolute values of them increased with increasing the temperature of the solutions. The adsorption of the RB19-RY145 binary mixtures to the cottonseed pulp was investigated at different temperature. In the binary adsorption of RB19-RY145 mixtures onto cottonseed pulp biosorbent, how the first component affected the adsorption equilibrium uptake of second component was investigated by changing the concentration of the first dye while the concentration of the second dye was kept constant. It was observed that the presence of RY145 in the medium decreased the adsorption of RB19 a adsorption. According to expermental results which are obtained at different temperatures for binary mixtures the evaluate of kinetic models showed that this data best fits the pseudo-second-order model and it was determined that the adsorption equilibrium data worked very well with the Langmuir isotherm model. The calculated entalpy value for binary mixture was found to be less than the calculated entalpy value for one component system. In addition, the calculated absolute value of free energy change value for binary mixture was found to be less than one component system. Keywords: Reactive Blue 19, Reactive Yellow 145, Dye, Adsorption, Cottonseed pulp
Removal of single and binary combinations of reactive blue 19 and reactive yellow 145 reactive dyes from aqua solutions
Keywords: Kimya Mühendisliği